2015
DOI: 10.4070/kcj.2015.45.3.242
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Spontaneous Multi-Vessel Coronary Artery Dissection and Celiac Disease

Abstract: Celiac disease (CD) is an immune-mediated enteropathy involving the small intestines. Genetic and environmental risk factors as well as autoimmunity have been linked to its etiology. Studies have shown that coronary artery disease, autoimmune myocarditis, arrhythmias and premature atherosclerosis are more prevalent in individuals with CD compared to individuals without the disease. In this case report a young male patient with CD presented with acute myocardial infarction with spontaneous coronary artery disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Laboratory evaluation for inflammatory or autoimmune conditions is generally low yield but may be considered in the post-MI setting, particularly in patients who have symptoms of or physical examination findings of autoimmune or rheumatologic disease. SCAD has been described in case reports of patients with various systemic inflammatory diseases, including systemic lupus erythematosus, 97–102 inflammatory bowel disease, 103 polyarteritis nodosa, 104 sarcoidosis, 52 celiac disease, 105 and cryoglobulinemia in the setting of hepatitis C. 106 In these series, underlying coronary vasculitis 100 or systemic inflammation 100 may have contributed to the risk of SCAD, and larger cohort studies have shown that at least a small proportion of patients have either underlying inflammatory diseases or short-term increases in inflammatory markers. 13,60 Taken together, these series indicate that underlying inflammatory conditions may be predisposing factors in the development of SCAD in a small proportion of patients.…”
Section: Pathogenesis Of Scad and Scad-associated Conditionsmentioning
confidence: 99%
“…Laboratory evaluation for inflammatory or autoimmune conditions is generally low yield but may be considered in the post-MI setting, particularly in patients who have symptoms of or physical examination findings of autoimmune or rheumatologic disease. SCAD has been described in case reports of patients with various systemic inflammatory diseases, including systemic lupus erythematosus, 97–102 inflammatory bowel disease, 103 polyarteritis nodosa, 104 sarcoidosis, 52 celiac disease, 105 and cryoglobulinemia in the setting of hepatitis C. 106 In these series, underlying coronary vasculitis 100 or systemic inflammation 100 may have contributed to the risk of SCAD, and larger cohort studies have shown that at least a small proportion of patients have either underlying inflammatory diseases or short-term increases in inflammatory markers. 13,60 Taken together, these series indicate that underlying inflammatory conditions may be predisposing factors in the development of SCAD in a small proportion of patients.…”
Section: Pathogenesis Of Scad and Scad-associated Conditionsmentioning
confidence: 99%
“…In adult CD patients lacking cardiovascular risk factors, abnormal homocysteine, erythrocyte sedimentation rate, C-reactive protein, and insulin levels may, along with inflammation, be contributive to arterial stiffening[ 9 ]. Spontaneous coronary artery dissections have been observed as a cause of acute myocardial infarction in CD patients[ 3 ]. There is also some support for an association between CD and cerebrovascular disease[ 13 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…Acute myocardial infarction with ST-elevation and spontaneous coronary artery dissection can occur in young patients with CD[ 3 , 136 ]. However, chronic hypocalcemia in untreated CD patients due to poor absorption of minerals can result in electrocardiographic changes that mimic acute myocardial infarction[ 120 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD causes a number of gastrointestinal problems, such as diarrhea, abdominal distention and malabsorption, due to the intake of grain proteins, which are collectively referred to as a "gluten" diet [1,2]. Cardiovascular symptoms, like arrhythmias or irregular heartbeats, coronary artery diseases, and possible heart failure, have also been also reported to be associated with CD [2][3][4][5][6]. Some studies have indicated that these symptoms are caused by inflammation, while others have suggested the involvement of the autoimmune system response [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%